2017
DOI: 10.1080/08869634.2017.1404285
|View full text |Cite
|
Sign up to set email alerts
|

The effect of specially designed and managed occlusal devices on patient symptoms of tinnitus: A cohort study

Abstract: Objective Bioesthetic maxillary anterior guided orthoses (BMAGOs) were designed and adjusted to establish the mandibular location referred to as stable seated condylar position SSCP. This study demonstrates treatment efficacy of this device on tinnitus. Methods All patients had histories of temporomandibular disorder (TMD), head, neck and shoulder pain. Each patient wore the BMAGO at all times, eating, talking and sleeping with it functioning as a surrogate occlusion. Patients were seen every two weeks for adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Although several cohort studies showed the positive effects of occlusal splint on otologic symptoms in TMD subjects, 31–35 the only available RCT in literature was conducted by Kuttila et al 23 . and showed the efficacy of the stabilisation splint therapy in alleviating otalgia secondary to TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Although several cohort studies showed the positive effects of occlusal splint on otologic symptoms in TMD subjects, 31–35 the only available RCT in literature was conducted by Kuttila et al 23 . and showed the efficacy of the stabilisation splint therapy in alleviating otalgia secondary to TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that both the MI and CR rarely coincide with each other in most cases, and estimates show that a 1.75 mm deviation is usually noticed between the two parameters in up to 90% of the general population. [6][7][8][9] Other parameters were also reported in the literature to consider when planning an orthodontic treatment approach. These include the vertical dimension, which should be maintained at a favorable point, in addition to establishing the lateral and immediate anterior guidance protocols before deciding and establishing the most appropriate treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…During examination of the patient the doctor should take into consideration any possible sources of deep pain and symptoms of TMD. If there is coexistent TMD and tinnitus, successful treatment of the former is likely to resolve or at least alleviate the patient's perception of tinnitus [3,16,21,23,24]. Selection of proper therapy should mainly depend on the coexistent TMD, maintaining the rule: "conservative therapy first".…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Patients with coexistent tinnitus with TMD should be treated by a dentist and physiotherapist [21]. The literature describes attempts at tinnitus treatment with physical therapy (manipulations, exercises, trigger point treatment) [15] and different occlusal appliances [23,24,26], all with positive results. Tinnitus improved in 43% [24] to 95% [23] of patients.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation